The level of protection provided by Chinese labour law compared to German labour law. - Moccia, Sergio M. (Diplomica Verlag, 2008)
AsienThis work describes the Chinese Labour Law and traces back the sources of the Chinese Labour Law regulations. In the first section, the German Labour Law and some of the most important clauses are explained. In further sections, the Chinese Labour Law itself and its coherent development, the main landmarks and the similarities to the German Labour Law, with its Romanist Tradition, are reflected. In particular the situation of the unions and their influence on management polices are named. Further more, this work displays the current situation in the Chinese corporate world and its relatio.